Emergency stress management among nurses: A lesson from the COVID‐19 outbreak in China–a cross‐sectional study. Issue 3 (19th November 2020) - Liao, Changju; Guo, Linghong; Zhang, Cuicui; Zhang, Meiqi; Jiang, Wenjing; Zhong, Ying; Lin, Qingfang; Liu, Yin
Abstract: Aims and objectives: To assess the level of stress response, self‐efficacy and perceived social support status of working nurses during the outbreak of the COVID‐19 and investigate potential factors affecting their stress. Background: The stress level of clinical nurses directly affects their physical and mental health and work efficiency. Design: This study was a cross‐sectional investigation, which was performed following the STROBE checklist. The current study was conducted in February 2020 by selecting clinical nurses from the Zigong First People's Hospital for investigation. Methods: At the peak of the COVID‐19 outbreak in China, we assessed clinical nurses with the Stanford Acute Stress Reaction Questionnaire, the General Self‐Efficacy Scale and the Perceived Social Support Scale. Specifically, the nurses were divided into three groups: (a) nurses supporting Wuhan; (b) nurses in the department of treating the COVID‐19 patients in our hospital (epidemic department); and (c) nurses in the general department without the COVID‐19 patients in our hospital (non‐epidemic department). Results: A total of 1092 clinical nurses were surveyed with 94 nurses in Wuhan, 130 nurses treating COVID‐19 patients in our hospital and 868 nurses working without direct contact with diagnosed COVID‐19 patients. The mean stress score of all surveyed nurses was 33.15 (SD: 25.551). There was a statistically significant difference in stress response scores between different departments. Noticeably, the nurses who went to support in Wuhan showed a weaker stress response than the nurses who stayed in our hospital (mean: 19.98 (Wuhan) vs. 32.70 (epidemic department in our hospital) vs. 34.64 (non‐epidemic department in our hospital)). In addition, stress was negatively correlated with general self‐efficacy and perceived social support. Conclusion: The present study suggested that the stress status of second‐line nurse without direct contact with diagnosed COVID‐19 patients was more severe than that of first‐line nurses who had direct contact with COVID‐19 patients. Relevance to clinical practice: Our study indicated the importance of psychological status of second‐line medical staff during the global pandemic.